An Advisory Opinion on Climate Change Obligations Under International Law: A Realistic Prospect?. (27th October 2022) - Barnes, Richard
Abstract: On 31 October 2021, an agreement was signed between Antigua and Barbuda and Tuvalu that established a commission with the power to request an advisory opinion from the International Tribunal for the Law of the Sea (ITLOS). Since ITLOS's advisory jurisdiction has been tested in only one case, I explain and evaluate the procedural obstacles facing this commission, as well as the potential questions it might submit to ITLOS. The analysis draws upon the jurisprudence of the International Court of Justice to indicate how ITLOS could articulate and apply its jurisdiction in an advisory case. I conclude that although there appear to be few insurmountable obstacles to securing ITLOS's jurisdiction, care must be taken by the Commission of Small Island States on Climate Change and International Law to ensure that the questions presented to ITLOS are carefully drafted so that ITLOS has no concerns over the judicial propriety of giving an advisory opinion.